The art of people : 11 simple people skills that will get you everything you want - Kerpen, Dave. (New York : Crown Business, 2016)
"In a world where we are constantly connected, and social media has become the primary way we communicate, the key to getting ahead is being the person others like, respect, and trust. Because no matter who you are or what profession you're in, success is contingent less on what you can do for yourself, but on what other people are willing to do for you. Here, through 53 bite-sized, easy-to-execute, and often counterintuitive tips, you'll learn to master the 11 People Skills that will get you more of what you want at work, at home, and in life."--
Understanding yourself and understanding people -- Meeting the right people -- Reading people -- Connecting with people -- Influencing people -- Changing people's minds -- Teaching people -- Leading people -- Resolving conflict with people -- Inspiring people -- Keeping people happy.
Keywords: Psychology, Industrial; Interpersonal relations; Interpersonal communication